The Influence of Transformational Leadership Style on Employee Performance through Job Satisfaction as a Mediating Variable - Hamid, Hendrawati; Alman, Alman (MSJ : Majority Science Journal, 2025)
This study aims to analyze the effect of transformational leadership style on employee performance, with job satisfaction as a mediating variable. Transformational leadership, which involves motivation, inspiration, and attention to individual employee needs, is believed to enhance performance through improved job satisfaction. Data were collected from 50 employees of PT. Sukses Makmur Surabaya using a quantitative method with path analysis. The results show that transformational leadership has a significant positive effect on job satisfaction (β = 0.613) and employee performance (β = 0.312). Additionally, job satisfaction has a significant positive effect on employee performance (β = 0.427). The Sobel test confirms that job satisfaction mediates the relationship between transformational leadership and employee performance with a Z value of 3.011 (p < 0.05). These findings suggest that job satisfaction boosts employee motivation and commitment, which in turn drives better performance. Practical implications of these findings are that organizations should focus on developing transformational leadership styles and creating a supportive work environment to improve both job satisfaction and employee performance.